Centralized red muscle in Odontaspis ferox and the prevalence of regional endothermy in sharks - Dolton, Haley R; Snelling, Edward P; Deaville, Robert; Jackson, Andrew L; Perkins, Matthew W; Bortoluzzi, Jenny R; Purves, Kevin; Curnick, David James; Pimiento, Catalina; Payne, Nicholas L (Royal Society, The, 2023)
The order Lamniformes contains charismatic species such as the white shark Carcharodon carcharias and extinct megatooth shark Otodus megalodon, and is of particular interest given their influence on marine ecosystems, and because some members exhibit regional endothermy. However, there remains significant debate surrounding the prevalence and evolutionary origin of regional endothermy in the order, and therefore the development of phenomena such as gigantism and filter-feeding in sharks generally. Here we show a basal lamniform shark, the smalltooth sand tiger shark Odontaspis ferox, has centralized skeletal red muscle and a thick compact-walled ventricle; anatomical features generally consistent with regionally endothermy. This result, together with the recent discovery of probable red muscle endothermy in filter feeding basking sharks Cetorhinus maximus, suggests that this thermophysiology is more prevalent in the Lamniformes than previously thought, which in turn has implications for understanding the evolution of regional endothermy, gigantism, and extinction risk of warm-bodied shark species both past and present.